KONSEP DASAR INOVASI PENDIDIKAN DAN GLOBALISASI - Jannati Aliyah; Miftahul Cholifah, Karoma, Mardiah Astuti (Jurnal Ilmu Pendidikan dan Kearifan Lokal, 2023)
This paper aims to describe and examine more deeply the concept of educational innovation and globalization regarding the notion of innovation, educational innovation education, and modernization in education and globalization. This study uses the library research method by critically and in-depth review of relevant library materials such as books and journals that are worthy of being used as references in the preparation of this paper. The data collection technique used in this paper uses secondary data, namely by collecting data indirectly by examining the object in question